1998
DOI: 10.4269/ajtmh.1998.59.606
|View full text |Cite
|
Sign up to set email alerts
|

Epifil: a dynamic model of infection and disease in lymphatic filariasis.

Abstract: Abstract. The lack of a quantitative framework that describes the dynamic relationships between infection and morbidity has constrained efforts aimed at the community-level control of lymphatic filariasis. In this paper, we describe the development and validation of EPIFIL, a dynamic model of filariasis infection intensity and chronic disease. Infection dynamics are modeled using the well established immigration-death formulation, incorporating the acquisition of immunity to infective larvae over time. The dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 45 publications
(82 reference statements)
0
85
0
Order By: Relevance
“…Our previous paper demonstrated that the observed distribution of infection intensity with age was consistent with the action of acquired immunity [18]. This mechanism is included in the model where it is assumed that past experience of infection results in a reduction in the rate of establishment of new infections.…”
Section: Conceptual Frameworkmentioning
confidence: 70%
See 4 more Smart Citations
“…Our previous paper demonstrated that the observed distribution of infection intensity with age was consistent with the action of acquired immunity [18]. This mechanism is included in the model where it is assumed that past experience of infection results in a reduction in the rate of establishment of new infections.…”
Section: Conceptual Frameworkmentioning
confidence: 70%
“…In this paper, we have attempted to develop a realistic transmission model for lymphatic filariasis by extending an earlier version of the EPIFIL model [18]. This is achieved by incorporating the age structure of the human community and the dynamics of infection within the vector population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations